Seis saltos que practicamos por los caminos de la complejidad social - Villasante, Tomás R. (Política y Sociedad, 2007)
It proposes a criticism of the excessive abstract theorifications on the social science debates about objectivisms, constructionisms, complexities, fluencies, etc. that still in the air and aren’t operative. It brings 6 concepts that have been aplicated in local participatives processes with some good outcomes in the last ten years. It also brings a diagram with the 6 jumps during the time, from epistemology knowledge to some reference techniques.